Self-Sampling of Oropharyngeal Swabs Among Healthcare Workers for Molecular Detection of Respiratory Viruses: A Valuable Approach for Epidemiological Studies and Surveillance Programs - Galli, Cristina; Pellegrinelli, Laura; Del Castillo, Gabriele; Forni, Giovanni; Gandolfi, Cecilia Eugenia; Mosillo, Marco; Pietronigro, Anna; Tiwana, Navpreet; Castaldi, Silvana; Pariani, Elena (Frontiers in Public Health, 2020)
This study aimed at assessing the validity of self-collected (self-sampled) oropharyngeal (OP) swabs among healthcare workers compared to those collected by trained sentinel General Practitioners (GP-sampled) from individuals with influenza-like illness (ILI), to be implemented in epidemiological studies and/or surveillance programs of viral pathogens involved in community respiratory infections. OP swabs were collected from adults (>18 years) with ILI during the 2018-2019 influenza season. Two groups of samples were considered: 1) 131 self-sampled OP swabs collected by healthcare workers after being trained on the sampling procedure; 2) 131 GP-sampled OP swabs collected from outpatients by sentinel GPs operating within the Italian Influenza Surveillance Network. To assess swabbing quality, following RNA extraction, each sample was tested for the presence of the human ribonuclease-P gene (RNP) by in-house real-time RT-PCR. Samples with cycle threshold (Ct) <35 were considered adequate for further virological analysis. Influenza virus (IVs), Respiratory syncytial virus (RSV) and Rhinovirus (RV) genomes were detected by in-house real-time RT-PCR. All samples were positive to RNP detection with Ct<35. The mean Ct value was similar in the two groups (group 1 vs group 2: 25.93±2.22 vs 25.46±2.40; p=0.10). IVs-, RSV- and RV-positivity rates were 26.7% vs 52.7% (p<0.01), 7.6% vs 9.9% (p=0.52) and 21.4% vs 19.9% (p=0.76), respectively. Self-sampled OP swabs resulted as valid as GP-sampled OP swabs for molecular detection of respiratory viruses. Self-swabbing can thus be a worthwhile strategy for sample collection to implement molecular surveillance of respiratory pathogens and carry out epidemiological studies, easily reaching a larger population size.